Elaboração e Análise de Projetos na Gestão Pública / Preparation and Analysis of Projects in Public Management - Morais, David Maycon Ribeiro; Silva, Thiago Sousa (ID on line. Revista de psicologia, 2022)
Resumo: No que diz respeito aos efeitos da terceirização no mercado de trabalho brasileiro, o presente artigo pretende compreender as causas dos efeitos, nas relações de trabalho envolvendo funcionários terceirizados na administração pública, algo que tem se demostrado um problema significativo e frequente na sociedade brasileira. Portanto, a lógica foi explorar materiais elaborados sobre o tema, artigos científicos, sites, livros, indicadores estatísticos e na legislação, com intuito de encontrar uma solução acreditável, capaz de sanar os reveses encontrados na atual lei da terceirização (Lei nº 13.429/2017) e contribuem para colocar o trabalhador em situação de vulnerabilidade. Dito isso, é imperioso encontrar uma solução aos problemas encontrados, para se valer a dignidade da pessoa humana onde é uns dos princípios basilares na Constituição Federal de 1988. Palavras-chave: Administração Pública. Gestão Pública. Gestão de Projetos. Abstract: Project management is characterized as a strategic and fundamental practice for the public sector in the search for efficiency and distance that involve excessive bureaucratization processes, delays or non-compliance with deliveries and the waste of public resources. The objective of the present study is to illustrate the representativeness of the elaboration and analysis of projects in public management. To support and structure this investigation, bibliographic research was carried out, this technique aims to systematize lines of thought about a subject. The bibliographic research was fundamental to understand different perspectives in the face of phenomena such as the analysis of the public sector and the role of Administration, project management concepts and the management of risk, people and time. The results of this study showed that, in order to carry out a project, soon after the decision to implement it, it is of paramount importance to have financial resources, commonly resources with limited budget availability, which have a cost for society and for the which some benefit to the community in general is sought. Thus, it is recommended to carry out preliminary studies on the use of these resources in the area of Public Administration. Finally, it is concluded that project management in the public sector stems from a need to evolve and consolidate an efficient management model, so the elaboration and analysis of projects in public management carried out with commitment and organization offers some benefits, they are cost reduction; improvement in personnel management; transparency in processes; ease in creating strategic plans; identification of the main problems and the possibility of using specific software. Keywords: Public Administration. Public administration. Project management.